Study The Effect Of Feed Withdrawal And Adding Dried Bakery Yeast In The Diet On ph And Some Microbial Types Of Broiler Chickens Intestine - AL-Hamiari, Maha A. (The Iraqi Journal of Veterinary Medicine, 2007)
This study has been conducted to study the effect of feed withdrawal and adding dried bakery yeast on pH and some microbial indicators which includes Total Bacterial Count (TBC) ,Coliform Count (CC) , Fungi Count (FC) and Lactobacilli Count (LC) in the gastro -intestinal tract of 45 marketed broiler chickens at 8 weeks of age .The birds randomly distributed into three treatments and each treatment to three replicates (15 birds per replicate ) which were: un -treated control (T1) , broiler chickens subjected to feed withdrawal 8 hrs. before slautered (T2) , broiler chickens fed a diet contained 1% of dried bakery yeast three days before subjected to feed withdrawal 8 hrs. before slautered (T3 ) . The data obtained revealed thefollowing :-No statically differences in the pH of gastro -intestinal tract were appeared due to feed withdrawal and adding dried bakery yeast . Feed withdrawal (T2) caused a significant (p<0.05) increase in TBC ,TC and FC in the intestine content compaired with T1 and T3 . Adding 1% of dried bakery yeast three days before subjected to feed withdrawal 8 hrs. before slautered (T3) caused a significant (p<0.05) decreased in TBC,CC and FC , in themean time LC significantly (p<0.05) increased .